Defining the mechanism of polymerization in the serpinopathies. - Ekeowa, U; Freeke, J; Miranda, E; Gooptu, B; Bush, M; Pérez, J; Teckman, J; Robinson, C; Lomas, D (2010)
The serpinopathies result from the ordered polymerization of mutants of members of the serine proteinase inhibitor (serpin) superfamily. These polymers are retained within the cell of synthesis where they cause a toxic gain of function. The serpinopathies are exemplified by inclusions that form with the common severe Z mutant of α(1)-antitrypsin that are associated with liver cirrhosis. There is considerable controversy as to the pathway of serpin polymerization and the structure of pathogenic polymers that cause disease. We have used synthetic peptides, limited proteolysis, monoclonal antibodies, and ion mobility-mass spectrometry to characterize the polymerogenic intermediate and pathological polymers formed by Z α(1)-antitrypsin. Our data are best explained by a model in which polymers form through a single intermediate and with a reactive center loop-β-sheet A linkage. Our data are not compatible with the recent model in which polymers are linked by a β-hairpin of the reactive center loop and strand 5A. Understanding the structure of the serpin polymer is essential for rational drug design strategies that aim to block polymerization and so treat α(1)-antitrypsin deficiency and the serpinopathies.